X-ray spectroscopy on ultrafast-decaying core-excited atomic ions. Issue 11 (January 2020) - Ilchen, M; Mazza, T; Baumann, T M; Boll, R; De Fanis, A; Grychtol, P; Music, V; Ovcharenko, Y; Rivas, D; Berrah, N; Erk, B; Gryzlova, E; et al.
Synopsis: Results from the first soft X-ray user experiment at the European XFEL on nonlinear photon-matter interaction will be presented. Angle-resolved electron time-of-flight spectroscopy employed at the AQS (Atom-ic-like Quantum Systems) endstation of the SQS (Small Quantum Systems) instrument reveals insight into the character of resonances in highly transient, core ionized neon ions, i.e. Ne + 1s 1 2s 2 2p 6 → Ne + * 1s 0 2s 2 2p 6 np, together with their respective relaxation dynamics. Enabled by the unique properties of the European XFEL, novel perspectives on efficient nonlinear spectroscopy will be discussed.